Implementation of E-Tickets in the Prosecution of Traffic Violations in Denpasar City (A Study of the Ticket Hearing Process at the Denpasar District Court) - I Nengah Wirna; A.A Sagung Poetri Paraniti; Ida Bagus Anggapurana Pidada (Sharia Oikonomia Law Journal, 2023)
The development of the times makes everything no longer need to be done manually. This provides convenience to all parties in doing work, including traffic police. Nowadays, the police no longer need to ticket traffic violators directly. The police can simply give an e-ticket to the offender. E-tickets are the application of tickets that only use photographic evidence on cellphones. This research examines the implementation of e-ticketing in traffic violation court hearings in Denpasar City and the legal consequences arising from the use of e-ticketing. Using a normative-empirical legal approach, this study analyzes the system of traffic violation enforcement using Electronic Traffic Law Enforcement (ETLE) and the implementation of e-ticketing in court hearings. The findings show that e-ticketing has successfully improved the effectiveness of law enforcement and compliance with traffic regulations. The sanctions imposed on violators are based on applicable laws, including fines and administrative measures. This research also highlights the importance of professional and non-discriminatory law enforcement, as well as public awareness of the importance of traffic safety.